ELABORAÇÃO DE UMA AVALIAÇÃO FISIOTERAPÊUTICA PARA USO EM SALA DE RECUPERAÇÃO PÓS ANESTÉSICA - Coracini, Maria A.; Marchi, Genara J. D.; Klahr, Patrícia d. S.; Windmöller, Pollyana; Souza, Regina M. H. d.; Eickhoff, Heloísa M.; Pasqualoto, Adriane S. (Salão do Conhecimento, 2013)
Resumo